Consumer Participation in Self-Production: The Role of Control Mechanisms, Convenience Orientation, and Moral Obligation. Issue 2 (2nd April 2016) - Thi Xuan Mai, Huynh; Ottar Olsen, Svein
Abstract : Consumers participate in self-production when they actively create output products/services. Based on a cognitive antecedents–motivation–behavioral framework, this study tests how different control mechanisms, convenience orientation, and moral obligation relate to self-production involvement and behavior in a sample of 415 households in the home meal preparation context. The proposed model is tested using structural equation analysis. The results show that desire for control influences self-production behavior indirectly through self-production involvement, while perceived behavioral control influences behavior more directly. Convenience orientation is important for predicting self-production involvement, while moral obligation has significant effects on both self-production involvement and behavior.